Derivation of the clonal‐cell lines from Siberian sturgeon (Acipenser baerii) head‐kidney cell lines and its applicability to foreign gene expression and virus culture. Issue 5 (12th March 2018) - Ryu, J. H.; Kim, M. S.; Kang, J. H.; Kim, D. H.; Nam, Y. K.; Gong, S. P.
Abstract : This study was conducted to establish and characterize the clonal‐cell lines from Siberian sturgeon Acipenser baerii head‐kidney tissues and to evaluate its applicability as a research tool. From the culture of A. baerii head‐kidney derived cells, 10 cell lines were established first and then eight clonal‐cell lines were derived from clonal growth and colony expansion of two cell lines that showed significant high colony‐forming ability. All eight clonal‐cell lines were morphologically similar and grew stably under monolayer culture but their growth rates were significantly different. They possessed diploid DNA contents, expressed epithelial cell‐related genes and showed strong anchorage dependency to substrates. When a clonal‐cell line was transfected separately with three plasmid vectors including fluorescent reporter genes driven by cytomegalovirus, marine medaka Oryzias dancena β‐actin or A. baerii β‐actin promoter, the cell lines expressed fluorescent signals regardless of promoter types. The cells harbouring foreign genes could be expanded to stable cell lines under drug selection and then they additionally could form the extensively proliferating colonies at low‐density culture. Finally, the clonal‐cell lines showed the susceptibility to viral haemorrhagic septicaemia virus (VHSV). Collectively, the clonal‐cell lines from A. baerii head kidney were established and these cell lines will be able to provide an excellent in vitro system for various biological studies in this fish species.